Investigation of Drug–Drug Interactions Between Ritobegron, a Selective β3‐Adrenoceptor Agonist, With Probenecid in Healthy Men. Issue 3 (29th September 2015) - Abe, Yoshikazu; Nakano, Yuki; Kanazawa, Toru; Furihata, Takao; Endo, Takuro; Kobayashi, Mamoru
Abstract: We evaluated the effects of probenecid, a potent organic anion transporter 1 (OAT1) and OAT3 inhibitor, on the pharmacokinetics and safety of ritobegron, a selective β3 ‐adrenoceptor agonist, in healthy men. Twelve healthy men were administered a single oral dose of ritobegron (20 mg) alone or in combination with probenecid 2 hours before administration of ritobegron. In the combination sequence, additional doses of probenecid were administered 4 and 10 hours after the administration of ritobegron. Probenecid increased the Cmax of KUC‐7322, an active form of ritobegron, and the AUC0–48  h by 1.39 and 2.93 times, respectively. Probenecid prolonged the t1/2 of KUC‐7322 from 1.6 to 3.4 hours and decreased the renal clearance and cumulative fraction of KUC‐7322 excreted in urine from 18.5 to 4.9 L/h and from 64.7% to 49.7%, respectively. Coadministration of probenecid did not influence adverse events, blood pressure, pulse rate, or heart rate relative to ritobegron alone. Although probenecid inhibited renal tubule secretion of KUC‐7322 via OAT3 and increased KUC‐7322 exposure, it did not influence adverse effects or vital signs. Therefore, clinically significant drug–drug interactions are unlikely to occur when probenecid is administered in combination with OAT3 inhibitors or substrates.